Foster care in the perspective of parental authority and the best interests of the child. Selected issues - Kuna, Dominika (Studia Iuridica Toruniensia, 2021)
The aim of this study is to examine selected issues in the field of foster care. The text deals with the issue of exercising parental authority when the child is placed outside the family. The rights and obligations of parents and guardians were presented. The conclusions of individual parts also influenced the summary of the text from the perspective of interpreting the best interests of the child and its legal protection.